P21 'My identity had just been completely devastated' – experiences of adolescent and young adults with. (20th March 2019) - Martins, Ana; Bennister, Lindsey; Fern, Lorna; Gerrand, Craig; Onasanya, Maria; Storey, Lesley; Wells, Mary; Woodford, Julie; Windsor, Rachael; Whelan, Jeremy; Taylor, Rachel
Abstract : Background: Treatment of sarcoma often involves long-term hospitalisation, extensive surgery, loss of mobility, complex rehabilitation programmes, and is in many cases accompanied by low expectations of survival. Subsequently, poorer patient-reported outcomes are recorded in comparison to patients with other cancer types. Studies examining psychosocial functioning of those affected by sarcoma are needed to improve wellbeing. Aim: This study aims to explore the experiences of adolescents and young adults (AYA) with sarcoma. Methods: A total of 35 AYA diagnosed with soft-tissue and bone sarcoma (19 female) aged 13–39 years old (M=28.8; SD=6.7) participated in semi-structured telephone/face-to-face interviews (25 diagnosed within the previous 4 years; 4 had an amputation). Interviews were recorded and transcribed verbatim and analysed using Framework analysis. Results: The quality of life domains of physical, emotional and social wellbeing were the overarching themes of analysis. In addition to descriptions of the impact of sarcoma on these domains, results showed three influencing factors of AYA experience: healthcare professionals' role; social support and coping strategies. AYA described experiences of being reassured and receiving information at the right level from professionals. Healthcare professionals' expertise and accessibility was valued by AYA. Family, friends and interactions with peers with cancer were core elements of support. Adaptation after diagnosis, treatment and/or surgery was influenced by the way AYA dealt with stress and adversity, with some struggling with finding their 'new normal'. Rehabilitation and therapy/counselling services had a considerable role in AYA's physical and emotional wellbeing; however access to these services was not equitable. Conclusions: A sarcoma diagnosis disrupts normality and initiates a process of re-examining expectations for self, daily life, and future hopes and plans. This study shows the impact of sarcoma on AYA's wellbeing and identity development; protective/risk factors identified could guide future support interventions for AYA with sarcoma.